The cycloid type and its differentiation from core schizophrenia: a phenomenological approach - Sigmund, Dieter; Mundt, Christoph (Comprehensive psychiatry, 1999)
The heterogeneity within schizophrenia or the group of schizophrenias remains a vexing and limiting problem. An alternative to the “classic” explanatory construct of a schizophrenic unitary psychosis is the current concept of a positive/negative dichotomy with or without mixed type. However, the validation by findings from brain imaging, specificity, and prognostic validity of these multiple-entity approaches are still uncertain. Psychopathology is challenged to identify discrete types as homogenous as possible, providing closer relationship to distinct disease processes. Such types are to be defined by one or more axial syndromes, syndromes in an essential, not correlative, sense. One of these types is embraced by the term cycloid psychosis, implying a good prognosis. Using an integrative phenomenological methodology, the present study is able to show the specific quality of phenomena occurring in this type to pinpoint their “inner” relationships and to demonstrate cycloid syndromes as axial syndromes in the phenomenological sense. Thus, it is shown that positive symptoms in the cycloid type are different from those in core schizophrenia. In addition to the quality and inner coherence of the constituent elements, the absence of structural deformations of (1) emotional expression and affect, (2) thought, and (3) movement impulses and sequences is the decisive specificity feature that allows differentiation of the cycloid type from poor-prognosis core schizophrenia. These syndromes of structural deformations are the axial syndromes of core schizophrenia, occurring with or without “productive” (positive) phenomena. Its conceptualization makes a contribution to the actual negative-symptom discussion shifting the perspective from a low specific level (e.g., abulia) to phenomena of higher specificity. On the basis of a precise definition of cycloid axial syndromes, previous operationalization suggestions are reviewed and evaluated, and an alternative approach is outlined. Finally, it is hypothesized that the cycloid type may be a primary neurotransmitter disease, while core schizophrenia seems closer to the pathophysiological mechanisms described in Stevens' theory.
Gesehen am 27.01.2021